Teorema da esfera suave via fluxo de Ricci - Belli, Rafael da Silva (2023)
The goal of this dissertation is the theoretical development of the Ricci flow, a differential equation over a family of Riemannian metrics on an arbitrary differentiable manifold, and its use in the proof of the so-called Smooth Sphere Theorem, which states that every compact, simply connected Riemannian manifold with dimension greater than or equal to 4, with sectional curvature pinched between 0.25 and 1, is diffeomorphic to a sphere.